Phenological responses to climate warming in temperate moths and butterflies: species traits predict future changes in voltinism. Issue 7 (9th April 2020) - Teder, Tiit
Abstract : Changes in the number of generations per year (voltinism) have been among the most common phenological responses to climate warming in insects inhabiting seasonal environments. Nevertheless, numerous species have maintained univoltine (one generation per year) phenology with increasing temperatures, indicating the involvement of phylogenetic, ecological or some other constraints on phenological change. I examined geographic variation in voltinism in moths and butterflies of northern Europe to identify species traits that might predispose species to univoltine/multivoltine phenology. I focused on species with a wide latitudinal distribution range (15 degrees as a minimum) which makes it unlikely that constraints imposed by season length could preclude multivoltinism across their distribution. Almost half of the 731 moth and butterfly species considered appear to have a single generation throughout their entire European range. A univoltine life‐cycle across a wide latitudinal gradient suggests the presence of some constraint that makes additional generations either impossible or at least strongly disadvantageous, which will unlikely change with future climate warming. The scattered distribution of univoltine and multivoltine species across the lepidopteran phylogeny indicates that phylogenetic constraints do not strongly limit changes in voltinism, and the trait is open to ecologically‐driven adaptive evolution. My data show that species with one generation per year are generally larger than multivoltine species, but size forms no absolute constraint to having multiple generations per year. Obligately univoltine species dominate among egg and adult overwinterers (life‐histories typical of so‐called spring‐feeders), whereas species with capacity for multiple generations prevail among pupal overwinterers. Multivoltinism is also infrequent among species feeding on grasses, particularly in endophagous grass‐feeders. Larval diet breadth has no discernible effect on voltinism. Given the diverse ecological consequences of voltinism and its changes, accounting for the species' capacity for multivoltinism may be a key to address future challenges in biodiversity conservation and pest management.